Methods of detecting biochemical substances contained in the sedan plant (Eurasian Scientific Herald, 2022)
The growth of a healing sedan is widely used in folk medicine. Ibn Sino and Giyosdin Algerians studied the medicinal properties of the sedan plant and used it in folk medicine. Today, xalgae-resistance methods of treating sedan growth have been approved by medicine. In addition, Ibn Sino, O.Sodiqov, A.Kholmatov, and U.S.A